Le spectacle sportif, l’héroïsation et la construction du genre - Robin Recours; Sylvain Ferez (Communication)
In France, a woman's place in the real (or objective) world of sports institutions has been widely studied. However few empirical studies have investigated her place in the perceived (or subjective) world of spectators. The authors questioned 878 students from two levels of secondary education in the Provence, Alpes, Côte d'Azur Region in Southern France. The results show that men occupy a majority position in the "Pantheon" of the most liked athletes regardless of the gender of the selected students but not for the same reasons. Male teenagers chose male sports celebrities for reasons of athletic prowess: female teenagers chose male sports celebrities for aesthetic reasons.